ANALISIS PERHITUNGAN BIAYA PRODUKSI BERDASARKAN PESANAN (JOB ORDER COSTING) PADA RAFI JAYA MEBEL (RJM) SUAK TEMENGGUNG - Handayani, Emi Siti; Winarni, Winarni; Akiah, Siti; Suriyanti, Linda Hetri (Research in Accounting Journal (RAJ), 2020)
If management in a company is well managed, it will certainly provide greater benefits in terms of company progress. Where the direction of thinking is clear in applying economic principles. The formulation of the problem in this study is for a production system based on work orders, where costs are accumulated based on work that imposes costs using a system approach to determining the cost of the order (Job Order Costing). The research method used is descriptive quantitative through survey research, observation interviews and documentation on objects. The results show that based on the calculation results it is known that the determination of the estimated production cost of an order can be utilized as one of the basis for determining the selling price that will be charged to the customer. In addition, the estimated production cost information is also useful as one of the bases to consider whether an order is accepted or not. The smaller the production costs to be set, the greater the selling price to be set. By determining the cost of production it will cover expenses or production costs, so that losses can be reduced by the company. For the production of retro teak tables, the estimated selling price charged to the buyer is Rp. 4,800,000, with an estimated production cost of Rp. Rp 3,900,000, and the actual production cost of Rp 3,968,000. So it can be concluded that the determination of the estimated selling price and the estimated production costs affect the determination of the production costs at Rafi Jaya Furniture Suak Temenggung. Using a Job order costing sheet card to make it easy to record costs directly to the base price card, the production order number must be listed above the order cost card.